2007
DOI: 10.1021/jp077226+
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Solute Dynamics in Room Temperature Ionic Liquids

Abstract: The excitation wavelength dependence of the emission kinetics of several solutes is used to demonstrate the presence of dynamic heterogeneity in two representative room temperature ionic liquids, dimethyl-isopropyl-propyl-ammonium bis(trifluoromethylsulfonyl)imide [N(ip311)(+)][Tf(2)N(-)] and N-propyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide [Pr(31)(+)][Tf(2)N(-)]. The solute kinetics examined here include rotation and solvation of coumarin 153, isomerization of two malononitriles, and intramole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
195
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(214 citation statements)
references
References 53 publications
14
195
5
Order By: Relevance
“…Jin et al 136 showed that rates for both photoinduced intramolecular electron-transfer of crystal violet lactone ͑CVL͒ and photoisomerization of malonitriles were dependent on the excitation wavelength in dimethyl-isopropyl-propyl-ammonium/͓NTf 2 ͔ − . Annapureddy and Margulis 137 performed computational studies on CVL in a related IL, revealing that the kinetics of intramolecular electron transfer between the locally excited and charge transfer states of CVL in the IL is local solvent-environmentdependent due to slow solvent relaxation.…”
Section: Heterogeneity Of Reaction Dynamics In Ilsmentioning
confidence: 99%
“…Jin et al 136 showed that rates for both photoinduced intramolecular electron-transfer of crystal violet lactone ͑CVL͒ and photoisomerization of malonitriles were dependent on the excitation wavelength in dimethyl-isopropyl-propyl-ammonium/͓NTf 2 ͔ − . Annapureddy and Margulis 137 performed computational studies on CVL in a related IL, revealing that the kinetics of intramolecular electron transfer between the locally excited and charge transfer states of CVL in the IL is local solvent-environmentdependent due to slow solvent relaxation.…”
Section: Heterogeneity Of Reaction Dynamics In Ilsmentioning
confidence: 99%
“…The departure results are in agreement with the values of β (0 ≤ β ≤ 1) obtained from the stretched exponential fitting, as shown in the inset of Figure 6, which typically reflects the heterogeneity of the cosolvent mixture, as the smaller value of β represents the more significant heterogeneity. 16 Therefore, as the TEGDME molecules interact with the ionic liquid [bmim] [PF 6 ] within the nonpolar incompact and polar compact domains, the microviscosity of the mixtures is enhanced in contrast with both of the two neat compositions when the TEGDME mole fraction is 0.1 and the heterogeneous structure mainly remains in the ionic liquid enrichment phase of the mixture.…”
Section: Rotational Dynamics Of C153mentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34] Detailed knowledge of the dielectric behaviour of RTILs is particularly important since such properties are critical for understanding their solvation dynamics. [16,18,19] Unfortunately, the picture that has emerged from dynamics studies to date is unsatisfactory. [16][17][18] For example, it has been found that dielectric continuum models, which successfully describe the frequencydependent dielectric response of polar molecular liquids, [35] miss a considerable part of the fast solvation dynamics of RTILs.…”
Section: Introductionmentioning
confidence: 99%